TAHLIL AL-QANUN FI AL-QISHAT AL-QASHIRAT “AL-NAJM AL-KABIR” LI ZAHIRAT AL-BAILY ‘ALA ASAS NADHARIYYAT ROLAND BARTHES - Ardiyanti, Titin; Abyad, Habil; Tsauro, Muhammad Ahalla (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2023)
The conveyance of messages in short stories is not only done explicitly but also implicitly by using implicit language. Therefore, semiotics is an appropriate theory to explain the meaning of a literary work so that it can express the message contained in the literary work. This study aims to describe 5 codes according to Roland Barthes in the short story an-Najm al-Kabir. The method used in this research is descriptive qualitative research method. Data obtained from reading and note-taking techniques. The results of the analysis show that the five codes according to Roland Barthes are used in the short story al-Najm al-Kabir. From the results of the study, it can be concluded that the code that is often used in al-Najm al-Kabir's short story is proaretic code as many as 7. Hermeneutic, symbolic, semikic, and cultural codes are only found around 1-3 only. The code of action makes the story run well, with the hermeneutic code it also makes the readers interested in finding answers in the story presented. As well as the presence of other codes to make the stories presented more lively and fun.